Optimisation study on the drain mode of cycloidal rotor oil pump. (4th October 2022) - Wang, Wen; Liu, Xiang; Cai, Hao; He, Shanghong; Li, Yuelin
In order to optimise the internal flow field pulsation characteristics of a cycloidal rotor oil pump, the internal oil drain structure of the pressure limiting valve was changed to an external oil drain structure. The numerical simulation method is used to calculate the internal flow field of the cycloidal oil pump with different drain structures. The outlet pressure pulsation, pressure pulsation at the pressure limiting valve, displacement of the pressure limiting valve spool and cavitation are compared and analysed. The results show that, relative to internal drain structure, the pressure amplitude of the external drain structure at the pressure limiting valve is reduced by 30%, the pressure amplitude at the outlet is reduced by 25%, and the cavitation phenomenon at the interface between the pressure limiting valve and the inlet cavity is eliminated. The bench test is carried out to verify the sample pump, and the test results are in good agreement with the simulation results, with the volume efficiency improved by up to 4%.